2005
DOI: 10.1056/nejmsa042088
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Screening for HIV in the United States — An Analysis of Cost-Effectiveness

Abstract: In all but the lowest-risk populations, routine, voluntary screening for HIV once every three to five years is justified on both clinical and cost-effectiveness grounds. One-time screening in the general population may also be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
400
1
12

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(423 citation statements)
references
References 21 publications
10
400
1
12
Order By: Relevance
“…[20][21][22] Normalizing HIV testing in the minds of the general public is important. Freely available materials in the proper language and educational level should accompany Asians=Pacific Islanders, American Indians=Alaska Natives, and persons of multiple races were excluded because numbers were too small for meaningful analysis.…”
Section: Individuals With Dates Of Initial Hiv Diagnosis In Southmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Normalizing HIV testing in the minds of the general public is important. Freely available materials in the proper language and educational level should accompany Asians=Pacific Islanders, American Indians=Alaska Natives, and persons of multiple races were excluded because numbers were too small for meaningful analysis.…”
Section: Individuals With Dates Of Initial Hiv Diagnosis In Southmentioning
confidence: 99%
“…Three recently published papers concerning the cost-effectiveness of HIV screening concluded that even when the prevalence of HIV infection in specific populations is substantially lower than 1%, screening for HIV is cost effective relative to other established screening programs. [20][21][22] And while the public health benefits are clearindividuals on therapy have more productive lives, avert opportunistic infections, as well as secondary transmissionsthe costs associated with routine screening are not trivial. Although most practitioners would agree that providing accessible testing benefits patients, the capacity of treatment and preventive services will need to be increased if routine HIV testing is to translate into earlier treatment.…”
Section: Individuals With Dates Of Initial Hiv Diagnosis In Southmentioning
confidence: 99%
“…Patients diagnosed and treated for HIV avoid hospitalizations and can reduce risky behaviors, further reducing HIV transmission 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This cost/ QALY rose to nearly $40 000/QALY with a seroprevalence of only 0.1%. The second study, by Paltiel, 21 demonstrated that the cost/QALY of one-time testing of patients with a 1% seroprevalence to be $38 000.…”
Section: Costmentioning
confidence: 99%
“…Finally, with the demonstrated added value of hospitalist programs 33 and the recent literature demonstrating the cost effectiveness of routine HIV testing, 20,21 hospitalists are well suited to demonstrate leadership in the acquisition of the resources required to make routine inpatient HIV testing possible.…”
Section: Hospitalists At the Helm Of Routine Inpatient Hiv Testingmentioning
confidence: 99%